The effectiveness of complementary baby massage therapy on weight gain in stunting toddlers - Dessy Ratna Sari; Deby Chyntia Yun; Henny Rista; Eva Donna; Sri Rezeki (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Stunting remains a chronic nutritional problem in Indonesia, impacting the growth and development of infants. Low appetite and inadequate food intake are major contributing factors to stunting. One non-pharmacological intervention with the potential to improve appetite and digestive function is infant massage, which is considered safe, easy to implement, and sustainable in the community. Purpose: To analyze the effect of infant massage on eating patterns and weight gain in stunted toddlers. Method: This study used a quasi-experimental design, dividing respondents into an intervention group and a control group. The intervention group received structured infant massage six times over two weeks, followed by one-month follow-up. Data collection included an appetite assessment questionnaire and anthropometric measurements to assess changes in toddler weight. Results: The study results showed that stunted toddlers who received regular infant massage for two weeks experienced significant increases in appetite and weight gain after a one-month follow-up period compared to the control group. Infant massage has been shown to be effective in stimulating appetite and supporting weight gain in stunted toddlers. Conclusion: Infant massage can be used as an effective complementary intervention in stunting management programs, particularly in improving dietary patterns and increasing the nutritional status of stunted toddlers.